Atividade sísmica histórica na região Centro-Oeste do Brasil, com ênfase na bacia sedimentar do Pantanal, no período de 1982 a 2020 - STONE MARISCO DUARTE (2022)
The present work aims to carry out a historical survey of the seismic activities in the Midwest region of Brazil, with emphasis on the Pantanal Sedimentary Basin during the period 1982 to 2020. For the survey of historical records, the printed newspapers were used as research sources, made available by the digital libraries of the National Library of Rio de Janeiro and the newspaper Correio do Estado /MS, through its digitalized collection and because it is an important press organ of the region. In the searches through the searched media, no unpublished seismics were found, only earthquakes that complement the data provided by the Brazilian Seismographic Network (RSBR), which is operated by five centers: Institute of Astronomy, Geophysics and Atmospheric Sciences of the University of São Paulo (IAG-USP), Seismological Observatory belonging to the University of Brasilia (UNB), National Observatory of Rio de Janeiro (ON), Federal University of Rio Grande do Norte (UFRN) and Federal University of Mato Grosso do Sul (UFMS). It was also possible to analyze the earthquake of November 6, 2015, in the region of Miranda MS, through the reports collected by questionnaires and audio recordings, whose material was used as a case study, with the identification of the seismic intensity, in a qualitative way, of the tremors using the Modified Mercalli scale classification. This seismic intensity classification was compared with the magnitude, obtained by treating the records from stations AQDB (Aquidauana, MS), SALV (Santo Antônio de Leverger, MT) and PP1B (Sonora, MS).